Optimization of culture conditions to obtain maximal growth of penicillin-resistant Streptococcus pneumoniae (2005)
ABSTRACT: Background Streptococcus pneumoniae, particularly penicillin-resistant strains (PRSP), constitute one of the most important causes of serious infections worldwide. It is a fastidious microorganism with exquisite nutritional and environmental requirements to grow, a characteristic that prevents the development of useful animal models to study the biology of the microorganism. This study was designed to determine optimal conditions for culture and growth of PRSP. Results We developed a simple and reproducible method for culture of diverse strains of PRSP representing several invasive serotypes of clinical and epidemiological importance in Colombia. Application of this 3-step culture protocol consistently produced more than 9 log10 CFU/ml of viable cells in the middle part of the logarithmic phase of their growth curve. Conclusion A controlled inoculum size grown in 3 successive steps in supplemented agar and broth under 5% CO2 atmosphere, with pH adjustment and specific incubation times, allowed production of great numbers of PRSP without untimely activation of autolysis mechanisms.